Determination of Cocoa Powder Quality Produced by Small-Medium Enterprise Using Six Sigma Analysis - Hendy Firmanto; Yesi Kumalasari; Zikil Muarrofah (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2021)
Cocoa powder now has become a common craft product of small-medium processing enterprises (SME) in Indonesia. Small-medium enterprises developprocessing sequence in smaller quantity compared to big company, nonetheless it must follow the national cocoa powder standard of SNI 3737:2009. The aim ofthis experiment was to evaluate the SME cocoa process production performance through Six Sigma analysis of the product to comply the standard requirements.The cocoa powder product was evaluated using three critical to quality (CTQ) parameters involving water content, color, and fineness. National standard determinedthe maximum water content value is 5%, the color is brown or Agtron number 65 and minimum fineness percentage of particle (75 µm) must be 99.5%. This resultexplain the stability process of SME which is exceeding the control limit value of non conformity product. Its process capability showing the Sigma value of2.6 with defect per million value was 126,667. The CTQ parameters which contribute to the high non-conformity are fineness 78.95% and color 21.05%. The roughcocoa powder or fineness affects the highest non-conformity related to the high fat content in cocoa cake as input process and can be revised by upgrading thepressing machine performance.